1969
DOI: 10.1128/aem.17.6.923-924.1969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Spot-Indole Reagents

Abstract: Two spot-indole reagents, p-dimethylaminobenzaldehyde (DMABA) and pdimethylaminocinnamaldehyde, were evaluated quantitatively. Although fourfold less sensitive, DMABA proved to be more stable and economical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Three biochemical tests, Voges-Proskauer (VP) ( 48 ), lysine decarboxylase ( 49 ), and indole ( 50 ), were used to confirm the evidence of the presence of enteric bacteria and to differentiate E. coli from other Enterobacteriaceae ( 51 ). The presumptive E. coli isolates were grown (i) in methyl red-VP (MR-VP) medium (Difco) and tested for acetoin production using Voges-Proskauer reagent (BioMérieux) according to the manufacturer’s instructions, (ii) on decarboxylase medium base (Difco) supplemented with l -lysine (Sigma) to test for l -lysine utilization, and (iii) in L-broth to test for tryptophan utilization using Remel indole reagent (Thermo Scientific) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Three biochemical tests, Voges-Proskauer (VP) ( 48 ), lysine decarboxylase ( 49 ), and indole ( 50 ), were used to confirm the evidence of the presence of enteric bacteria and to differentiate E. coli from other Enterobacteriaceae ( 51 ). The presumptive E. coli isolates were grown (i) in methyl red-VP (MR-VP) medium (Difco) and tested for acetoin production using Voges-Proskauer reagent (BioMérieux) according to the manufacturer’s instructions, (ii) on decarboxylase medium base (Difco) supplemented with l -lysine (Sigma) to test for l -lysine utilization, and (iii) in L-broth to test for tryptophan utilization using Remel indole reagent (Thermo Scientific) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The DMACA reagent proved to be the most sensitive spot-test indicator of indole production in this study, and was shown to be more sensitive than DMABA with facultative bacteria by Lowrance and coworkers. 1 We observed also that in tests with Bacteroides melaninogenicus, the black pigment which was not apparent while growth was on the solid medium became obvious on the test papers and obscured the pink to red color reaction with Kovacs', DMABA, and Patho-Tec I strips. The blue or green reaction with DMACA spread away from the blackened cellular material and was easy to see.…”
Section: Discussionmentioning
confidence: 62%
“…The azafulvenium chloride salt, in aqueous solutions, absorbs in the visible region (500-700 nm) with a maximum centered at 624 nm and displays a high extinction coefficient value (86,666 mol −1 • L• cm −1 [18], 97,000 ± 13,000 mol −1 • L• cm −1 (this work)). In the presence of tryptophan, another condensation reaction occurs, which yields a red-violet product, absorbing at 563 nm [19]. In culture media, such as Lysogenic Broth or Buffered Peptone Water, which both contain tryptophan, both reactions occur and the absorption bands of the two products overlap.…”
Section: Probe Choice and Interferencesmentioning
confidence: 99%